1951
DOI: 10.6028/nbs.bms.121
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of failures of white-coat plaster

Abstract: An investigation was made of a particular kind of plaster failure that is characterized by the formation of blisters or bulges in the finish coat of plaster. Extensive surveys revealed that the failures are widespread; that several years elapse before the bulges appear and thereafter the number and extent of failures increase as the age of the buildings increases; that the failures occur more extensively and rapidly during warm humid weather; and that there is a marked similarity in the failures regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1953
1953
1953
1953

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In the investigation of white-coat plaster failure by W ells, Clarke, Newman, and Bishop [5], it was shown that the failures were caused by the delayed hydration and resulting expansion of the magnesia in the dolomi tic lime. It was also shown by Wells, Clarke, and Levin [6], in their study of th e expfinsive characteristics of hydrated limes and the development of a test for soundness, that expansion of the autoclaved bars was dependent not only on the amount of unhydrated magnesia but also on the 14 strength of the test specimens.…”
Section: Results Of Testsmentioning
confidence: 99%
“…In the investigation of white-coat plaster failure by W ells, Clarke, Newman, and Bishop [5], it was shown that the failures were caused by the delayed hydration and resulting expansion of the magnesia in the dolomi tic lime. It was also shown by Wells, Clarke, and Levin [6], in their study of th e expfinsive characteristics of hydrated limes and the development of a test for soundness, that expansion of the autoclaved bars was dependent not only on the amount of unhydrated magnesia but also on the 14 strength of the test specimens.…”
Section: Results Of Testsmentioning
confidence: 99%
“…Studies [4] have been in progress for several years at the National Bureau of Standards of a particular type of plaster failure, associated only with regularly hydrated dolomitic limes and characterized by the formation of bulges, or large blisters, in the white-coat. It has been found that this type of failure results from a delayed expansion of the set, white-coat plaster.…”
Section: Introductionmentioning
confidence: 99%